Hubungan Pengetahuan Ibu Tentang Bermain Dengan Perkembangan Motorik Kasar Pada Anak Toddler - Ayu Dian Pratiwi; Irdawati Irdawati (Universitas Muhammadiyah Surakarta, 2017)
The number of countries that are experiencing problems such as delays in motor development will lead to declining creativity in adapting and a lack of understanding of the parents about the play. Parents' knowledge about factors play can influence the development of children's motor skills, especially motor rough. Objective: Aim to know the relationship mother’s knowledge of play with toddler gross motoric development at Posyandu of Suruhkalang village of KaranganyarType of this research is a descriptive quantitative research approach to cross-sectional correlation. The sample of this research is the mother who has children aged toddler (1-3 years) in Suruhkalang village of Posyandu total of 68 respondents. Taking samples use proportional random sampling. Instrument research using questionnaires for knowledge about playing and rough use motor development assessment Questionnaire Pre Screening developments . Analysis statistic uses Chi-Square test. Results of analysis of unknown value OR = 2,839 and value p = 0,222. The results of the analysis concluded there is no relationship mother’s knowledge of play with toddler gross motoric development at Posyandu of Suruhkalang village of Karanganyar